Glycomic and glycoproteomic analysis of serum from patients with stomach cancer reveals potential markers arising from host defense response mechanisms. - Bones, J; Byrne, J; O'Donoghue, N; McManus, C; Scaife, C; Boissin, H; Nastase, A; Rudd, P (2011)
Despite the reduced incidence of gastric cancer in the developed world, a diagnosis of stomach carcinoma still carries a poor prognosis due to the asymptomatic nature of the disease in the early stages, subsequent advanced stage diagnosis, and a low 5 year survival rate. Endoscopy remains the primary standard for diagnosis of stomach carcinoma and the current marker, carbohydrate antigen 19-9 (CA19-9) lacks the levels of sensitivity and specificity required in order to make it clinically useful for diagnostic monitoring. Therefore, there is a current need for additional markers to improve the diagnostic accuracy for the early stages of stomach cancer. Together, glycomic, proteomic, and glycoproteomic analyses of serum have the potential to identify such probable markers. A discovery study is reported here using preoperative serum from 80 stomach cancer patients, 10 patients bearing benign stomach disease, and 20 matched controls. Glycomic analysis of the total and immunoaffinity depleted serum revealed statistically significant increases in the levels of sialyl Lewis X epitopes (SLe(X)) present on triantennary glycans accompanied by increased levels of core fucosylated agalactosyl biantennary glycans present on IgG (referred to as the IgG G0 glycoform) which are associated with increasing disease pathogenesis. Protein expression analysis using 2D-DiGE returned a number of differentially expressed protein candidates in the depleted serum, many of which were shown to carry triantennary SLe(X) during subsequent glycomic investigations. Biological pathway analysis of the experimental data returned complement activation and acute phase response signaling as the most significantly altered pathways in the stomach cancer patient serum. Upon the basis of these findings, it is suggested that increased expression of IgG G0 and complement activation are a host response to the presence of the stomach tumor while the increased expression of SLe(X) and acute phase response proteins is a result of pro-inflammatory cytokine signaling, including IL-6, during carcinogenesis. The approach presented herein provides an insight into the underlying mechanisms of disease and the resulting changes in the glycome and glycoproteome offer promise as potential markers for diagnosis and prognostic monitoring in stomach cancer.